Holistic Nursing: A Handbook For Practice (Sixth Edition) - Dossey, Barbara Montgomery; Keegan, Lynn; Guzzetta, Cathie E. (Jones and Bartlett Learning, 2020)
Important Notice: The digital edition of this book is missing some of the images or content found in the physical edition. This market-leading resource in holistic nursing is published in cooperation with the American Holistic Nurses Association (AHNA). Each chapter is revised and updated by contributors from the best-selling Fifth Edition, as well as new thought leaders from the field of holistic nursing